Laghouat, La ville assassinée ou le point de vue de Fromentin de Lazhari LABTER entre témoignage colonial et réappropriation postcoloniale - : DILMI Zahia (جامعة محمد بوضياف المسيلة, 2025)
Abstract This research paper takes as its starting point the analysis of the memorial and postcolonial dimensions of the Génocide contemporary Algerian novelLaghouat, la villeassassinéeou le point de vue de Fromentin (2018) by LAZHARI Labteret. The problematic of our study targets, through a hybrid narrative mixing fiction, colonial archives and various resources of oral tradition and Algerian culture that reconstructs the Laghouat genocide, the mechanisms by which literature can become a space of memorial reparation and narrative resistance. Our analysis, structured around three axes centered on the fictionalization of history, critical intertextuality, and the novel's artistic and memorial significance, is based on an interdisciplinary approach combining postcolonial theory, the aesthetics of memory and the theory of intertextuality, with the aim of uncovering a form of committed Algerian novel writing that is a vehicle for resilience, intergenerational transmission and the reconstruction of identity.
Keywords: Keywords: Genocide - poscolonialism - memory - resilience